درجة توافر عناصر الأمان والسلامة في المؤسسات الصحية دراسة حالة مستشفى شهداء الأقصى - Ibrahim Abushariaa, A.S.; AbuJarad, I. (Universiti Sains Islam Malaysia, 2024)
Safety is a prerequisite for working in organizations. This study aimed at finding out the degree of availability of safety elements in health institutions. The descriptive analytical method was used. The study tool was a questionnaire, which was applied to a random sample of (67) employees. The results showed that the level of care of the management of Al-Aqsa Martyrs Hospital by providing safety measures for the workers came at a relative weight (71%). The relative weight of the total degree of safety and physical safety measures was 63.58% while the availability of safety and practical safety in Al-Aqsa Martyrs Hospital came in an average (62.44%). In addition, there was no statistically significant difference between the mean responses of respondents regarding the availability of safety and security elements at Al-Aqsa Hospital due to the gender variable, level of work, scientific qualification, years of service and nature of work. In the light of the study results, the researcher pressed on the necessity to design buildings, offices and sections in a way that ensures smooth work and taking in consideration the need of professional health requirements, appropriate temperatures and ventilation in design.